Features of the formation of vocal and stage skills among students of Chinese universities in the process of learning opera singing - He Chang; Natalya G. Tagiltseva (Управление культурой)
The article attempts to identify the features of opera performance training in bachelor's degree programs in higher educational institutions in China, where the process of formation of vocal and stage skills occupies a central place. The relevance of the research is determined by the recently increased popularity of music education in China, including opera, which is of value to the Chinese and world cultural foundation. The actual material of the study was the curricula for the bachelor's degree program «Opera Performance» of Changchun Pedagogical University, Tanhuang University and the Beijing Central Conservatory. Using the method of analyzing theoretical material and generalization, the key professionally oriented disciplines, the essence of vocal and stage skills formed by students in the learning process were identified. Based on the works of Chinese researchers, the state and problems of vocal and stage training of future opera performers in Chinese universities were revealed. The conclusions of the study can be useful for Chinese and Russian researchers of the peculiarities of the Chinese opera pedagogical school.